2018
DOI: 10.5603/kp.a2018.0153
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery dilatation during normal pregnancy

Abstract: Our study shows pulmonary artery dilatation in healthy pregnant women without any other abnormal echocardiographic findings. These changes in PAD are associated with volume overload and low vascular resistance, and during postpartum they usually subside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…A recent prospective cohort study found that pregnant women who were obese demonstrated impaired myocardial function, measured by end-systolic wall stress, left ventricle cardiac index, and left ventricle mass index, compared with women who were not obese. 57 These researchers also showed that women with obesity had higher blood pressure readings, systemic vascular resistance measures, and pulsatility index scores than the control group, particularly between 25 and 30 weeks’ gestation. In another study, researchers followed 614 women who initiated recommended aspirin therapy before 16 weeks’ gestation for preeclampsia prevention.…”
Section: Resultsmentioning
confidence: 96%
“…A recent prospective cohort study found that pregnant women who were obese demonstrated impaired myocardial function, measured by end-systolic wall stress, left ventricle cardiac index, and left ventricle mass index, compared with women who were not obese. 57 These researchers also showed that women with obesity had higher blood pressure readings, systemic vascular resistance measures, and pulsatility index scores than the control group, particularly between 25 and 30 weeks’ gestation. In another study, researchers followed 614 women who initiated recommended aspirin therapy before 16 weeks’ gestation for preeclampsia prevention.…”
Section: Resultsmentioning
confidence: 96%
“…A TTE study of 69 consecutive healthy women with singleton pregnancies found that pulmonary artery diameter increased in all women from a mean of 20 mm at the end of first trimester to a mean of 22.7 mm at the start of third trimester [50]. The gestational pulmonary artery dilatation resolved postpartum to a mean value of 19.5 mm.…”
Section: E10mentioning
confidence: 98%
“…During normal pregnancy, systemic and pulmonary vessels dilate, resulting in decreased systemic (SVR) and pulmonary vascular resistance (PVR). Study has found that pulmonary artery dilatation in healthy pregnant women is common which is associated with volume overload and low vascular resistance [3].…”
Section: Introductionmentioning
confidence: 99%